Conceptualising the Role of Opinion Leaders as Moderator to Local Communities Commitment in Corporate Social Responsibility (CSR) Communication - Ammar Redza, Ahmad Rizal; Dayang Aizza Maisha, Abang Ahmad; Humaira, Raslie (Universiti Kebangsaan Malaysia, 2022)
Corporations are subjected to high criticism due to the misuse of Corporate Social Responsibility (CSR) communication to shelter their wrongdoing in running business activities. Obtaining trust from the local communities will increase corporations’ chances to earn Social Licence to Operate (SLO). Although communication is typically a two-way process, in communication research, getting a response from the targeted personnel is much more valuable. However, extant studies provide insufficient understanding related to communicative framework in engaging with local communities. Current research trends in CSR communication are skewed towards the effects of CSR communication, legitimacy of CSR communication, as well as the challenges in carrying out CSR communication. In this study, the current model of communication which is based on the mechanistic perspective of communication is discussed and expanded. Three important communication elements are analysed, and their relationship is proposed to form a new conceptual framework that includes a fourth element: opinion leader. The suggested framework primarily describes and provides arguments for the extent of communication willingness in affecting communication commitment. The crux of this framework is communication quality; transpiring in three formative factors namely bi-directional communication, symmetrical information and transparency. This framework believes that investigating the role of opinion leader in moderating the success of CSR communication adds empirical insights in the emerging literature of CSR communication. The discussed framework could be implemented in understanding dialogue between corporations and local communities.